Some problems in the theory of early universe evolution - Sannikov-Proskuryakov, S.S. (Вопросы атомной науки и техники, 2007)
We continue consideration of physical characteristics of early Universe. Here our attention is concentrated on the three topics: thermodynamics, relic helium, energy of physical vacuum.